The Singular Evolution of Olea Genome Structure - Mascagni, Flavia; Barghini, Elena; Ceccarelli, Marilena; Baldoni, Luciana; Trapero, Carlos; Díez, Concepción Muñoz; Natali, Lucia; Cavallini, Andrea; Giordani, Tommaso (Frontiers in Plant Science, 2022)
The current view of plant genome evolution proposes that genome size has mainly been determined by polyploidisation and amplification/loss of transposons, with a minor role played by other repeated sequences, such as tandem repeats. In cultivated olive (Olea europaea subsp. europaea var. europaea), available data suggest a singular model of genome evolution, in which a massive expansion of tandem repeated sequences accompanied changes in nuclear architecture. This peculiar scenario highlights the importance of focusing on Olea genus evolution, to shed light on mechanisms that led to its present genomic structure. Next generation sequencing technologies, bioinformatics and in situ hybridisation were applied to study the genomic structure of five related Olea taxa, which originated at different times from their last common ancestor. On average, repetitive DNA in the Olea taxa ranged from ~59% to ~73% of the total genome, showing remarkable differences in terms of composition. Among repeats, we identified 11 major families of tandem repeats, with different abundances in the analysed taxa, five of which were novel discoveries. Interestingly, overall tandem repeat abundance was inversely correlated to that of retrotransposons. This trend might imply a competition in the proliferation of these repeat classes. Indeed, O. paniculata, the species closest to the Olea common ancestor, showed very few tandem-repeated sequences, while it was rich in long terminal repeat-retrotransposons, suggesting that the amplification of tandem repeats occurred after its divergence from the Olea ancestor. Furthermore, some tandem repeats were physically localised in closely related O. europaea subspecies (i.e., cultivated olive and O. europaea subsp. cuspidata), which showed a significant difference in tandem repeats abundance. For 4 tandem repeats families a similar number of hybridisation signals were observed in both subspecies, apparently indicating that, after their dissemination throughout the olive genome, these tandem repeats families differentially amplified maintaining the same positions in each genome. Overall, our research identified the temporal dynamics shaping genome structure during Olea speciation, which represented a singular model of genome evolution in higher plants.